2009
DOI: 10.4103/0971-9261.59604
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic assisted anorectal pull through: Reformed techniques

Abstract: Aim:To assess the modifications in the technique of laparoscopic assisted anorectal pull through (LAARP) practiced at our institute and analyze the post operative outcome and associated complications.Materials and Methods:A retrospective study from January 2001 to May 2009 analyzing LAARP for high anorectal malformations.Results:A total of 40 patients - 34 males and six females, in the age group of two months to six years were studied. Staged procedure was done in 39 patients; one child with recto vestibular f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…The tunnel formation in LAARP was done under laparoscopic visualization and perineal muscle electrostimulation with or without laparoscopic muscle electrostimulation. The perineal dissection was done either bluntly using artery forceps or needle was placed in the center of the muscle complex, followed by balloon catheter dilation [4,6,10,11, Step Veress needle with a radially expanding sheet was another technique used to create the tunnel [12,14].…”
Section: Resultsmentioning
confidence: 99%
“…The tunnel formation in LAARP was done under laparoscopic visualization and perineal muscle electrostimulation with or without laparoscopic muscle electrostimulation. The perineal dissection was done either bluntly using artery forceps or needle was placed in the center of the muscle complex, followed by balloon catheter dilation [4,6,10,11, Step Veress needle with a radially expanding sheet was another technique used to create the tunnel [12,14].…”
Section: Resultsmentioning
confidence: 99%
“…[ 7 ] Anchoring the rectum with pre-sacral fascia is believed to prevent RMP in addition to lengthening of cutaneous anal canal by providing cephalad retraction, although some studies did not perceive that benefit. [ 3 7 ] In our initial three cases, we did not do presacral fixation and there was higher incidence of mucosal prolapse. Then, we believed in rectal fixation in all the remaining cases.…”
Section: Discussionmentioning
confidence: 98%
“…When compared to APPT, LAARP provides benefits such as avoidance of laparotomy, excellent visualisation of pelvis, less post-operative pain and simultaneous treatment of associated disease like cryptorchidism. [ 3 ] Although the long-term results of LAARP are yet to be interpreted, mid-term results from a study showed better defecation function with LAARP than PSARP. [ 4 ] LAARP results in earlier appearance of recto anal inhibitory reflex than PSARP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations